Population Dynamics in Muslim Countries Assembling the Jigsaw - Groth, Hans.; Sousa-Poza, Alfonso; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The book discusses the demographic changes in Muslim countries. It thereby focuses on topics such as the demographic dividend and the demographic transition, labour market challenges, health care, universal education and gender issues. These challenges are addressed at a country level and include policy implications for the large majority of the Muslim countries covered in this book. Moreover, political consequences for Europe with respect to the integration of Muslims are presented to the reader.
Introduction and Overview -- Topics and Issues -- Country and Regional Studies -- Policy Implications -- Statistical Annex -- Biographical Sketches.
Keywords: Social sciences; Development Economics; Economic policy; Population; Social policy; Migration; Demography; Social Sciences; Demography; Population Economics; Development Economics; Economic Policy; Migration; Social Policy